THE ROLE OF SOCIAL MEDIA MEDIATION OF LEADERSHIP ON THE ORGANIZATIONAL PERFORMANCE OF SMEs - Dian Mala Fithriani Aira; Sry Rosita; Efvy Zamidra Zam (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
Â In the current era of digitalization, SMEs are required to adapt quickly according to technological developments and increasingly complex consumer needs. . The role of the leader can create a comfortable environment that can encourage increased employee performance to something that contributes to increasing national income in micro, small and large companies. One way to adapt and develop a business that is currently popular is to use social media-based content marketing. The main objective of this research is to determine the role of social media in mediating the influence of leadership on the SMEâ€™S performance organization. This study uses a literature and field research design with a quantitative causal approach. Collecting data in the field using a questionnaire measured by several questions related to social media, leadership, and organizational performance. For data analysis using the PLS method and data collection technique using proportionate stratified random sampling. Â